Changes in Hemodynamics and Tissue Oxygenation Saturation in the Brain and Skeletal Muscle Induced by Speech Therapy – A Near-Infrared Spectroscopy Study - U. Wolf; F. Scholkmann; R. Rosenberger; M. Wolf; M. Nelle (The Scientific World Journal)
Arts speech therapy (AST) is a therapeutic method within complementary medicine and has been practiced for decades for various medical conditions. It comprises listening and the recitation of different forms of speech exercises under the guidance of a licensed speech therapist. The aim of our study was to noninvasively investigate whether different types of recitation influence hemodynamics and oxygenation in the brain and skeletal leg muscle using near-infrared spectroscopy (NIRS). Seventeen healthy volunteers (eight men and nine women, mean age ± standard deviation 35.6 ± 12.7 years) were enrolled in the study. Each subject was measured three times on different days with the different types of recitation: hexameter, alliteration, and prose verse. Before, during, and after recitation, relative concentration changes of oxyhemoglobin (Δ[O2Hb]), deoxyhemoglobin (Δ[HHb]), total hemoglobin (Δ[tHb]), and tissue oxygenation saturation (StO2) were measured in the brain and skeletal leg muscle using a NIRS device. The study was performed with a randomized crossover design. Significant concentration changes were found during recitation of all verses, with mainly a decrease in Δ[O2Hb] and ΔStO2 in the brain, and an increase in Δ[O2Hb] and Δ[tHb] in the leg muscle during recitation. After the recitations, significant changes were mainly increases of Δ[HHb] and Δ[tHb] in the calf muscle. The Mayer wave spectral power (MWP) was also significantly affected, i.e., mainly the MWP of the Δ[O2Hb] and Δ[tHb] increased in the brain during recitation of hexameter and prose verse. The changes in MWP were also significantly different between hexameter and alliteration, and hexameter and prose. Possible physiological explanations for these changes are discussed. A probable reason is a different effect of recitations on the sympathetic nervous system. In conclusion, these changes show that AST has relevant effects on the hemodynamics and oxygenation of the brain and muscle.